Positive interactions of major-effect QTLs with genetic background that enhances rice yield under drought - Sandhu, Nitika; Dixit, Shalabh; Swamy, B.P. Mallikarjuna; Vikram, Prashant; Venkateshwarlu, Challa; Catolos, Margaret; Kumar, Arvind (Springer, 2018)
To improve the grain yield of the lowland-adapted popular rice variety Samba Mahsuri under reproductive-stage drought (RS) and to understand the interactions between drought QTLs, two mapping populations were developed using marker-assisted selection (MAS) and marker-assisted recurrent selection (MARS). The mean grain yield of pyramided lines (PLs) withqDTY2.2 + qDTY4.1in MAS is significantly higher under RS and irrigated control than lines with single QTLs. Among MARS PLs, lines with fourqDTYs(qDTY1.1 + qDTY2.1 + qDTY3.1 + qDTY11.1) and two QTLs (qDTY1.1 + qDTY11.1) yielded higher than PLs with otherqDTYcombinations. The selected PLs showed a yield advantage of 0.3–2.0 t ha−1under RS. An allelic profile of MAS PLs having sameqDTYcombination but with different yields under drought was studied. Hierarchical clustering grouped together the selected lines with high yield under drought. Epistasis test showed the interaction ofqDTY4.1andqDTY9.1loci withqDTY7.1significantly increased yield under drought and all the lines with higher yield under drought possessed the conserved region ofqDTY7.1on chromosome 7. The positive interactions among QTLs, effectiveness of QTLs in different backgrounds, introgression ofDTYQTLs together with resistance to biotic stresses shall help enhance grain yield under RS.